Compulsive behaviors in the workplace - Deciu, Valeriu (Advances in Social Sciences Research Journal, 2021)
Compulsive behaviors are psychiatric challenges that interfere with the regular life practices of those who exhibit them. This study qualitatively identified compulsive behaviors within three organizations located in no.2 major cities from Romania, aiming to explore their effects on workers’ productivity and extended community, including coworkers and employers. To understand the exact behaviors, a literature search was done from Google Scholar to understand examples of compulsive behaviors in the workplace before gathering data from the participants. Using three organizations, from construction materials and adjacent industries, 15 participants were selected and agreed to be interviewed. Further, a survey questionnaire was used to explore the severity and effect of the behaviors on productivity at work. The main results noted workplace compulsive behaviors like repetitive cleanliness, ritualistic behaviors like repetitive ordering or organizing things in a particular manner, persistent repetition of certain words or actions for the perfection of the work assigned, and isolation from other members. The findings from the results entailed an understanding that most compulsive behaviors conflict with established workplace code of conduct. Also, employees confirmed their continued struggle to control the exhibited behaviors. The effects of the behaviors on the employees’ productivity and time management were also highlighted. Importantly, most participants confirmed that most employers and coworkers understand their situations and provide social support.